ANALISIS KARAKTERISTIK DAN MOTIVASI SOSIAL EKONOMI PETANI KAPULAGA DI LAHAN PERHUTANI KABUPATEN BANYUMAS - Zulkifli, Lutfi; putri, dindy darmawati; Wijayanti, Irene Kartika Eka; Setiawati, Indah (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Cardamom is a leading export commodity. The demand for cardamom continues to increase from year to year, where the increase in cardamom production is inseparable from the role of farmers as the main actors in supporting cardamom productivity. This study aims to analyze the characteristics and socio-economic motivations of cardamom farmers in Pekuncen and Kedungbanteng Districts, Banyumas Regency, Central Java. This research was conducted using descriptive analysis method using a Likert scale. Determining the number of respondents was carried out using stratified random sampling technique,where in this study the number of respondents was 97 farmers. The results of this study are that the majority of cardamom farmers are male and are of productive age. Cardamom farmers have the last education in elementary school (SD) and are in the low education category. Cardamom farmers have only started cultivating cardamom in less than 5 years. The average cardamom farmer has a family of 3-5 people. The socio-economic motivations that encourage farmers to cultivate cardamom are divided into three, namely economic, psychological and sociological motivations. Cardamom farmers in Pekuncen and Kedungbanteng Districts are driven by economic motivation which is in the moderate category. The majority of cardamom farmers are in the low category for fulfilling psychological motivation in cultivating cardamom. Cardamom farmers are driven by sociological motivation which is in the high category.